2022
DOI: 10.1007/s10067-022-06087-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk of COVID-19 in patients with rheumatic diseases: a systematic review and meta-analysis

Abstract: Objectives COVID-19 pandemic has already had a tremendous impact on the process of human society; the survival of mankind and the healthy living environment deterioration with the influence will last for many years. This meta-analysis aims to assess the risk of COVID-19 in patients with rheumatic diseases. Methods PubMed, Web of Science, Embase, China National Knowledge Infrastructure (CNKI), and Chinese Biomedical Database (CBM) were systematically searched with no lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
2
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
2
12
2
4
Order By: Relevance
“…These risk factors can also increase the risk of severe disease and death [8]. Other studies examining rheumatic diseases found a higher death rate and hospitalization [4,11] with the same risk factors (in addition to comorbidities such as hypertension, cardiovascular disease, and obstructive pulmonary diseases) for patients with underlying rheumatic diseases, of which old age and presence of comorbidities were consistent with our study as risk factors for hospitalization. The hospitalization rate in our study (43%) is similar to that reported in a study from the COVID-19 Global Rheumatology Alliance registry that investigated 600 patients from different countries [19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These risk factors can also increase the risk of severe disease and death [8]. Other studies examining rheumatic diseases found a higher death rate and hospitalization [4,11] with the same risk factors (in addition to comorbidities such as hypertension, cardiovascular disease, and obstructive pulmonary diseases) for patients with underlying rheumatic diseases, of which old age and presence of comorbidities were consistent with our study as risk factors for hospitalization. The hospitalization rate in our study (43%) is similar to that reported in a study from the COVID-19 Global Rheumatology Alliance registry that investigated 600 patients from different countries [19].…”
Section: Discussionsupporting
confidence: 90%
“…Although most people have mild to moderate flu-like symptoms, the disease becomes more severe in vulnerable populations like patients with underlying hypertension, lung disease, diabetes, cardiovascular diseases, or end-stage renal disease [2]. It can induce severe pneumonia leading to acute respiratory distress syndrome (ARDS) and respiratory failure or multiple organ failure and death in severe cases [3,4]. The severity of lung involvement on initial chest CT scans is reported to be associated with higher rates of adverse outcomes in patients with COVID-19 [5].…”
Section: Introductionmentioning
confidence: 99%
“…O papel dos agentes antireumáticos na infecção pela COVID-19 apresenta resultados muito heterogêneos, pois alguns autores concordam que esses medicamentos têm um efeito protetor sobre a infecção e redução de complicações (Grange et al, 2020;Shin et al, 2022;F. Wang et al, 2022), mas há também um risco maior na evolução clínica (Akiyama et al, 2020;D'Silva & Wallace, 2021;J.…”
Section: Resultadounclassified
“…AR, artrite reumatoide; LES, lúpus eritematoso sistêmico; ACG, arterite de células gigantes; SS, síndrome de Sjögren; SpA: Espondiloartrite4 DISCUSSÃOA avaliação do impacto da COVID-19 tem sido altamente controversa desde o início da pandemia, já que vários estudos demonstraram que, desafiando as pessoas com DRA, esses indivíduos correm um risco maior de COVID-19 positivo, hospitalização ou internação na UTI e morte(Ruscitti et al, 2021).A partir dos resultados relatados no início da pandemia,Grange et al (2020) mostraram uma menor incidência de infecção em pessoas com DRA e tratadas com medicamentos modificadores. Mas a meta-análise deWang et al (F. Wang et al, 2022) descreve uma alta incidência de COVID-19 em pacientes reumáticos, embora esses resultados variem entre regiões (Tabla 1).…”
unclassified
“…Это мнение практически не изменилось и в дальнейшем. Так, в последнем метаанализе показано, что распространенность COVID-19, а также связанная с ним потребность в госпитализации и смертность у пациентов с ревматическими заболеваниями остаются на высоком уровне, хотя подчеркиваются статистически значимые региональные различия [2].…”
unclassified